Platelets in the tumor microenvironment and their biological effects on cancer hallmarks - Chen, Lilan; Zhu, Chunyan; Pan, Fan; Chen, Ying; Xiong, Lei; Li, Yan; Chu, Xiaoyuan; Huang, Guichun (Frontiers in Oncology, 2023)
The interplay between platelets and tumors has long been studied. It has been widely accepted that platelets could promote tumor metastasis. However, the precise interactions between platelets and tumor cells have not been thoroughly investigated. Although platelets may play complex roles in multiple steps of tumor development, most studies focus on the platelets in the circulation of tumor patients. Platelets in the primary tumor microenvironment, in addition to platelets in the circulation during tumor cell dissemination, have recently been studied. Their effects on tumor biology are gradually figured out. According to updated cancer hallmarks, we reviewed the biological effects of platelets on tumors, including regulating tumor proliferation and growth, promoting cancer invasion and metastasis, inducing vasculature, avoiding immune destruction, and mediating tumor metabolism and inflammation.